Análise do processo de briefing aplicado a projetos arquitetônicos de pequeno porte - Karla Crsitina Garcia de Carvalho (2012)
This paper discusses the development of the Program of Needs in small architecture firms. In this context, the literature review seeks to understand the stage of Briefing (program of needs) within the design process, highlighting some international trends. The work was conducted via an exploratory case study that took place in six architectural small size firms, including interviews with members, document analysis and monitoring of the design process. This exploratory case study has shown that the process of Briefing is often done in a somewhat lesser standardized, interactive way, showing deficiencies in communication between the agents involved. On the other hand, architects have drawn their attention to the need of improving the process of Briefing and to better define the requirements and needs of their clients, as this is one of the advantages of this activity, as well as they seek to answer what the purpose of the work is, describe its problems and point out the benefits of its realization. Therefore, as the process of Briefing in small offices has only a few studies, this paper seeks to contribute to the theme, pointing out some preliminary results and suggesting some points of investigation.